2013
DOI: 10.1373/clinchem.2012.195297
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum and Urinary MicroRNAs in Children with Idiopathic Nephrotic Syndrome

Abstract: BACKGROUND MicroRNAs (miRNAs) are present in body fluids and may have the potential to serve as disease biomarkers. This study explored the clinical value of miRNAs in serum and urine as biomarkers for idiopathic childhood nephrotic syndrome (NS). METHODS We obtained serum samples from 159 NS children (24 steroid resistant and 135 steroid sensitive), 109 age/sex-matched healthy controls and 44 children with other kidney disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 35 publications
3
76
1
Order By: Relevance
“…For e.g., in experimental models of kidney fibrosis, the number of interstitial myofibroblasts was significant reduced by a demethylating agent, a histone deacetylase inhibitor, and anti-microRNA-21 therapy, noting that microRNA-21 unregulation has been reported in several animal and human CKD tissue samples. 34, 35, 36, 37 Epigenetic regulation of fibrotic responses provides a new way to investigate environmental influences on genetically regulated pathways, such as kidney fibrosis.…”
Section: Genetic and Epigenetics Regulation Of The Fibrotic Responsementioning
confidence: 99%
“…For e.g., in experimental models of kidney fibrosis, the number of interstitial myofibroblasts was significant reduced by a demethylating agent, a histone deacetylase inhibitor, and anti-microRNA-21 therapy, noting that microRNA-21 unregulation has been reported in several animal and human CKD tissue samples. 34, 35, 36, 37 Epigenetic regulation of fibrotic responses provides a new way to investigate environmental influences on genetically regulated pathways, such as kidney fibrosis.…”
Section: Genetic and Epigenetics Regulation Of The Fibrotic Responsementioning
confidence: 99%
“…To date, miRNAs are regarded as having critical roles in distinct biological processes, including development, differentiation and oncogenesis [17,18]. Thus the expression patterns of miRNAs may reflect the changes of pathophysiological states or progression of particular diseases [19]. Indeed, large differences in the expression profiles of miRNAs were reported in placental tissue or tissue- Abbreviations: miRNAs, microRNAs; CCNE2, cyclin E2; COX2, cyclooxygenase 2; IL, interleukin; MSCs, mesenchymal stem cells; PE, preeclampsia; TAB3, transforming growth factor-b-activated kinase 1 binding protein 3; NF-jB, nuclear factor jB;…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Furthermore, children with nephrotic syndrome revealed an increased serum level of miR-19b. 25 One might speculate whether such a change is linked with the diminished 11β-HSD2 activity reported by our group in patients with the nephrotic syndrome. 26 It is shown that miR190a upregulated by mechanical stress in podocytes 28 might be linked with the shear stress-mediated downregulation of 11β-HSD2.…”
Section: Discussionmentioning
confidence: 84%
“…Proangiogenic, nephritic syndrome [24][25][26] rno-miR-29b-3p 1.2×10 -3 Fibrotic pathway, collagen genes, Mmp2, Itgb1 of a specific mRNA. As clearly indicated in Table S1, different programs predict different members of the miRNA family to bind to the 3′-UTR of the HSD11B2 mRNA, an observation known for other genes.…”
Section: Discussionmentioning
confidence: 99%